Using mātauranga Māori to inform freshwater management - Harmsworth, Garth; Awatere, S.; Pauling, C. (Landcare Research Policy Brief, 2013)
Keywords: co-governance; environment; governance; hapū; iwi; kāwanatanga; local government; water management

Indigenous Māori knowledge and perspectives of ecosystems - Harmsworth, Garth R; Awatere, Shaun (Ecosystem services in New Zealand : conditions and trends, 2013)
A framework/model based on Māori knowledge, values and perspectives is presented that distinguishes ‘cultural values’ from ‘cultural services’ and extends the deﬁnition of cultural values across the whole ecosystem services framework. Māori aspirations and well-being are interdependent on ecosystems and ecosystem services. Ultimately Māori wish to use these ecosystem approaches and frameworks to increase participation and inclusion in decision-making, to achieve multidimensional aspirational goals and desired indigenous outcomes.
Keywords: decision making; environment; environmental management; planning; policy making